2018
DOI: 10.3389/fnagi.2018.00350
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia as a Risk Factor for Vascular Contributions to Cognitive Impairment and Dementia

Abstract: Behind only Alzheimer’s disease, vascular contributions to cognitive impairment and dementia (VCID) is the second most common cause of dementia, affecting roughly 10–40% of dementia patients. While there is no cure for VCID, several risk factors for VCID, such as diabetes, hypertension, and stroke, have been identified. Elevated plasma levels of homocysteine, termed hyperhomocysteinemia (HHcy), are a major, yet underrecognized, risk factor for VCID. B vitamin deficiency, which is the most common cause of HHcy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 89 publications
(104 reference statements)
2
82
0
2
Order By: Relevance
“…The effect of folate deficiency was also studied on the cytomorphology and the kinetics of proliferation of ovarian granulosa cells, and the epithelial cells lining the uterus, cervix and vagina of six sexually mature female rhesus monkey and showed degeneration of Graffian follicles with an increase in atretic and cystic follicles, accompanied by a depletion of granulosa cells and reduction or even absence of corpora lutea (5). The homocysteine is produced in all cells and can be produced by folate metabolism that is reduced to tetrahydrofolate which is then converted to 5, 10-methylenetetrahydrofolate (6). Several studies confirmed the presence of increased serum Hcy concentration in PCOS patients (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of folate deficiency was also studied on the cytomorphology and the kinetics of proliferation of ovarian granulosa cells, and the epithelial cells lining the uterus, cervix and vagina of six sexually mature female rhesus monkey and showed degeneration of Graffian follicles with an increase in atretic and cystic follicles, accompanied by a depletion of granulosa cells and reduction or even absence of corpora lutea (5). The homocysteine is produced in all cells and can be produced by folate metabolism that is reduced to tetrahydrofolate which is then converted to 5, 10-methylenetetrahydrofolate (6). Several studies confirmed the presence of increased serum Hcy concentration in PCOS patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes methylenetetrahydrofolate reductase (MTHFR), methionine synthase (MTR), methionine synthase reductase (MTRR) and reduced folate carrier 1 (RFC-1) participate in the folate metabolism. Single nucleotide polymorphisms (SNPs) can lead to modifications in enzymatic activities involved in the metabolic pathway of folate and may be implicated in the etiology of the PCOS, mainly in epigenetic changes such as alterations in DNA methylation pattern (4)(5)(6)8). Several literature reports showed that the MTHFR C667T and A1298C, MTR A2756G, MTRR A66G and RFC-1 A80G SNPs are genetic factors that can modify the activities of the folate metabolism enzymes (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that higher Hcy levels are involved in age-related cognitive deficits and various types of central nervous system disorders, including Alzheimer´s disease, Parkinson disease, multiple sclerosis, cerebrovascular diseases and strokes. [26] A review by Esther et al revealed a positive trend between cognitive decline and increased plasma Hcy concentrations in general population and in patients with cognitive impairments. [27] Homocysteine is produced in all cells, and mechanisms of Homocysteine-induced cognitive impairment include neurotoxicity and vascular injury.…”
Section: Clinical Risk Factors For Preoperative Cognitive Impairmentmentioning
confidence: 99%
“…Some studies suggest the post-translational modification of proteins by homocysteine, termed homocysteinylation, contributes to its toxicity, while others shown that homocysteinylation induces cellular damage via oxidative stress, as well as disrupts astrocytic end-feet. [26,28] Animal models have shown that high plasma levels of homocysteine contribute to ultrastructural changes to cerebral capillaries, endothelial damage, swelling of pericytes, basement membrane thickening, and fibrosis. [29] In keeping with the literature, patients in cognitive impairment group had a higher level of homocysteine, even though multivariate regression model did not find the difference.…”
Section: Clinical Risk Factors For Preoperative Cognitive Impairmentmentioning
confidence: 99%
“…Homocysteine (Hcy) is an intermediary in essential cellular pathways, and its metabolism depends on several vitamin cofactors, primarily B 6 , B 9 (folic acid), and B 12 . Deficiencies in one or more of these is therefore a common cause of elevated blood homocysteine, termed hyperhomocysteinemia (HHcy).This condition has long been recognized as a vascular risk factor and it has recently garnered considerable attention as a modifiable risk factor for Alzheimer's disease (AD) [1,2]. The normal human range for Hcy in plasma is generally considered to be less than 15 µM, with increasing levels categorized as moderate (15-30 µM), intermediate (30-100 µM), or severe (> 100 µM) HHcy.…”
Section: Introductionmentioning
confidence: 99%